Perancangan dan Penerapan Kendali Lampu Ruangan Berbasis IoT (Internet of Things) Android - Wisnu Widi Anggoro; Indrastanti R Widiasari (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Internet of Things (IoT) is a concept that aims to expand the benefits of internet connectivity continuously . Along with the development of the era, the Internet of Things is widely used for various fields with the intention to helping human’s life, one of them is an electronic device for room lights that can be controlled remotely by utilizing an internet connection and controlled via an android smartphone. This research was conducted with the aim of building a smart home control prototype using the NodeMCU ESP8266 module as a microcontroller and system controller by using a bot on the Telegram, an android application. Based on the results of the experiments that has been done, it can be concluded that the system can work well according to it purpose.